A Comparative Clinical Study of Chatuha Prasratika Basti and Satavari Ksira Paka in the Management of Kshina Shukra (Oligozoospermia). - Arun , N K; Sharma, Gyan Prakash; Sharma, Mahesh Kumar; Anagha , M S; Sharma, Meenakshi (International Research Journal of Ayurveda & Yoga, 2022)
Kshina Shukra is one of the abnormal condition of Shukradhatu in which qualitative as well as quantitative vitiation of Shukra occurs, it is caused by the Vata-Pitta Dosha. In modern science it can be correlated as Oligozoospermia. The term Oligozoospermia is defined on the bases count and motility, where the sperm count is <15 mill/ml of semen can be considered as Oligozoospermia. Basti is the main therapy for Vata related diseases. Charaka Acharya mentioned so-many Vrushya basti in Charakam sidhi sthana, among them Chatuha Prasratika Basti, explained as Parama Vrshya, so that this Basti was selected for the study. Satavari and Ksira is Vata-Pitta Shamaka and Vrushya so that Satavari Ksirapaka is selected for study.